Chalets as agroindustrial heritage: The sugar houses in tuman (Lambayeque, Peru) - Marchena Tafur, Aurora (2023)
This research analyzes the houses of Tumán, from the heritage point of view, with the aim of understanding their heritage values, from the perspective of their social actors. Based on a qualitative methodology and with a phenomenological design, defining the object, the subjects and the place. The analyzes carried out are based on the information obtained in the field, through face-to-face and virtual interviews. In addition, it is worth mentioning that the information was collected in situ, measuring, taking photographs and flying over the study site. As a result, the object presents various estimates by its subjects, with a predominance and even absence of values. To finally conclude, on the importance of the participation of social actors as patrimonial subjects, since it is they who determine the values that the object possesses, understanding in this sense that the value of a patrimonial object is not intrinsic, but extrinsic.